A Statistical Study to Determine the Factors of Vitamin D Deficiency in Men: the City of Baghdad as a Model - Suad Turky Ali1, Hind Tahir Qadir2, Shaimaa Khalid Moufak1, Mohammed Ali Mohammed Al-Badri3, Mohamme (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Exposure to sun in the sunny days for 10 to 15 minutes a day and two to three times a week is enough to get vitamin D requirements in the majority, but people with darker skin need to be exposed to sun for longer periods to get their vitamin requirements. The purpose of this research was to achieve a statistical study to know and determine the factors behind deficiency of vitamin D among men in Baghdad city in addition to knowing the most important diseases associated with its deficiency in order to inform and educate the community as well as to raise awareness of the society about the role of this vital vitamin, prevention of its deficiency and to propose appropriate treatment for it. Methods: The research was conducted in several private clinics in Baghdad throughout 2017. The investigation was including study of 500 cases of men who were randomly selected. The cases were divided according to age groups into two groups: the first group was (20-40) years, while the other group was (more than 40 years). Also, the cases were classified according to vitamin D level to sufficient, insufficient and deficient. Results: The results obtained from the study showed that the percentage of vitamin D insufficient and deficient were 69.6% and 18.8%, respectively, while the sufficiency percentage was the lowest and scored 11.6%. Common chronic diseases, such as high blood pressure and diabetes as well as sleep disorders and muscle fatigue, were also followed in the cases. The results illustrated that 47.6% of men cases had diabetes and 39% had high blood pressure, while 28.2% and 17.2% of them had muscular fatigue and sleep disorders, respectively. These chronic diseases and symptoms were related in one way or another with Vitamin D deficiency. Conclusion: Vitamin D can be given for preventive and therapeutic purposes.